2014
DOI: 10.1016/j.comppsych.2013.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition, symptoms and premorbid functioning in a First Episode Psychosis sample

Abstract: Significant metacognitive impairments are observed in chronic psychosis samples but metacognition is less understood in first episode psychosis (FEP). The current study explored correlations between metacognition, symptoms and premorbid functioning in an FEP sample. In a cross-sectional cohort study, individuals in the first 12 months of treatment metacognition were assessed with the Metacognition Assessment Scale-Revised version (MAS-R). Psychotic symptomatology, premorbid adjustment, and clinician rated serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 36 publications
3
51
1
5
Order By: Relevance
“…This is in line with many earlier findings (Nicolò et al, 2012). Only the relationship between negative symptoms and understanding others is significant in this study, which is consistent with former studies in both chronic and firstepisode psychosis samples MacBeth et al, 2013). Understanding of one's own mind has been found to be associated with metacognition in chronic samples, but not in first-episode samples.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is in line with many earlier findings (Nicolò et al, 2012). Only the relationship between negative symptoms and understanding others is significant in this study, which is consistent with former studies in both chronic and firstepisode psychosis samples MacBeth et al, 2013). Understanding of one's own mind has been found to be associated with metacognition in chronic samples, but not in first-episode samples.…”
Section: Discussionsupporting
confidence: 82%
“…If the association between understanding of one's own mind and negative symptoms becomes stronger over time, the diversity in time since onset of the disorder in the current study may be able to explain the non-significance of this association. The results of the current study combined with these earlier findings suggest that understanding of others might be more specific to the early stages of the disorder (MacBeth et al, 2013). The lack of association between metacognition and positive symptoms is consistent with a meta-analysis of Varese and Bentall (2011), who found that after controlling for emotional distress and other comorbid symptoms, hallucination-proneness is no longer significantly related to metacognition.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Associations were seen between multiple metacognitive domains and cortical thickness in right rostral middle frontal gyrus and right pars triangularis, providing partial support for our second hypothesis. Inspection of MAS scores indicated that our CHR participants were more Self-Reflective, scored higher on Understanding Others, showed greater Mastery as well as higher Decentration as compared to means reported in people with schizophrenia (Lysaker et al, 2008(Lysaker et al, , 2010Nicolo et al, 2012;Macbeth et al, 2014).…”
Section: Discussionmentioning
confidence: 77%